Status quo and influencing factors of cancer-related cognitive impairment in patients with bone metastasis (骨转移瘤患者癌症相关认知功能障碍现状及影响因素分析) - ZHAO Lingling (赵玲玲); ZHANG Xiaojuan (张晓娟); CHEN Ping (陈平); LU Xin (鲁鑫) (中西医结合护理)
Objective To explore the status quo and influencing factors of cancer-related cognitive impairment (CRCI)in patients with bone metastasis. Methods From December 2023 to December 2024, 139 patients with bone metastasis in Chongqing cancer hospital were selected by the convenience sampling method. The tools used were Function Assessment of Cancer Therapy- Cognitive Function(FACT-Cog), Hospital Anxiety and Depression Scale(HADS), brief fatigue inventory(BFI-C) and EORTC QLQ-BM22. Results Patients scored(101. 20±15. 37) points in FACT-Cog, ［8(6, 11)］ points in HADS-Anxiety, ［9(7, 12)］ points in HADS-Depression, ［7(1, 17)］ points in BFI-C, ［45(41, 52)］ points in EORTC QLQ-BM22. There were significant differences in FACT-Cog scores among patients with different age, education, comorbidity, sleep and self-care ability(P＜0. 05). FACT-Cog scores and dimensions of bone metastases were negatively correlated with anxiety, depression, fatigue and quality of life(P＜0. 05). Multiple linear regression analysis showed that age, education and depression jointly explained 38. 4% of the variation of CRCI. Conclusion Cancer-related cognitive dysfunction in patients with bone metastases requires further attention from medical staff. Age, education level, comorbidity, negative emotions (anxiety, depression), symptom burden (sleep disorders, fatigue, low self-care ability), and quality of life are important factors. While focusing on the improvement of physical function symptoms, attention should be paid to the screening and intervention of cognitive dysfunction. (目的 探讨骨转移瘤患者癌症相关认知功能障碍现状及其影响因素。方法 选择2023年11月—2024年11月于重庆某三级甲等肿瘤专科医院住院治疗的139例骨转移瘤患者, 采用癌症治疗功能评估-认知功能量表(FACT-Cog)、医院焦虑抑郁量表(HADS)、简明疲乏量表(BFI-C)、骨转移瘤患者生存质量调查问卷(EORTC QLQ-BM22)对其进行调查。结果 骨转移瘤患者FACT-Cog量表得分(101. 20 ± 15. 37)分, HADS量表焦虑维度得分［8(6, 11)］分, 抑郁维度得分［9(7, 12)］分, BFI-C量表得分［7(1, 17)］分, EORTC QLQ-BM22量表得分［45(41, 52)］分。不同年龄、文化程度、有无共病、睡眠、自理能力的患者的FACT-Cog量表总分比较, 差异有统计学意义(P＜0. 05); 骨转移瘤患者FACT-Cog量表总分及各维度评分与焦虑、抑郁、疲乏、生存质量均呈负相关, 差异有统计学意义(P＜0. 05); 多元线性回归分析显示, 年龄、文化程度、抑郁为患者癌症相关认知功能障碍的独立影响因素, 可解释癌症相关认知功能障碍 38. 4%的变异量。结论 骨转移瘤患者癌症相关认知功能障碍有待医护人员的进一步重视, 年龄、文化程度、共病、负性情绪(焦虑、抑郁)、症状负担(睡眠失调、疲乏、自理能力低下)、生存质量是重要的影响因素, 在关注躯体功能症状改善的同时, 应重视癌症相关认知功能障碍的筛查与干预。)